ANALISIS KREDIT INVESTASI PADA BANK PEMERINTAH DI KALIMANTAN BARAT - B01108055, CHYNTIA RAHAYU (Jurnal Pembangunan dan Pemerataan, 2013)
This study entitled "Analysis of Credit Investment In State Bank in West Kalimantan". Problems like the author adopted in this study is "How to influence regional gross domestic product, interest rate, and inflation to the Bank Credit InvestasiPada Government in West Kalimantan". The purpose of the study was to determine the effect of interest rates, inflation and gross regional domestic product of the investment loan in State Bank in West Kalimantan. In this study, the authors used descriptive method used to examine the relationship between independent variables (level of GDP), (interest rate), (inflation) to the dependent variable (investment credit), which later on though to reach a conclusion. The model used in this study is the multiple regression models. Also used statistical analyzes such as t tests to examine the relationship between variables and the R-square test to see how much percentage produketiga these variables on investment loans. From the research that has been conducted by the authors, it can be concluded that the gross regional domestic product and significantly positively related to the investment, while the inflation rate is positively related but not significantly and negatively related to the interest rate but significantly. The interest rate is an indicator that determines the interest of investors to invest.